Evolutionary dynamics of value co-creation within the industry-university-research network: A multi-agent game perspective - Xuemin Zhang; Haijun Wang; Sardar M. N. Islam; Xiangfei Meng (PLoS ONE, 2025)
This paper investigates the evolutionary dynamics of value co-creation and defines the roles of multiple agents within the industry-university-research (IUR) network. A distinctive evolutionary game model from a multi-agent perspective is proposed to capture the previously under-explored dynamics of value co-creation within the IUR network. Furthermore, China’s high-end manufacturing industry was selected to establish the IUR network for simulation analysis because of its rapid transition toward innovation-driven value co-creation and the availability of granular data on IUR partnerships. The evolutionary game analysis yields three key findings with specific implications: Firstly, it reveals that the network’s average positive co-creation probability is inversely correlated with the enterprise investment difference and the academic knowledge input disparity between positive and negative value co-creation. This inverse relationship, identified by the game model, underscores the critical need for an effective supervision and management mechanism to optimize the utilization of enterprise investment and academic knowledge input during the value co-creation process within the IUR network. Secondly, the evolutionary game analysis demonstrates that specific parameters within the model – namely, the enterprise’s knowledge absorption capacity, the academic institution’s R&D capability, the government’s subsidy and penalty, and the intermediary’s transformation coefficient – play crucial roles in enhancing value co-creation probability. Based on these model-driven insights, we conclude that a combination of government guidance and market mechanisms serves as a sustainable driver for promoting value co-creation within the network. Thirdly, the model establishes an inverted U-shape relationship between the enterprise’s benefit distribution coefficient and the average positive co-creation probability. This critical finding from the evolutionary game simulation highlights the advantage of establishing an impartial interest distribution mechanism between industry and academia to foster synergy and stability in value co-creation within the IUR network.